Balanced Scorecard (BSC) role And Six Sigma in improving strategic performance A sample study of the members of the General Company for Northern Cement - ثابت, الاء وضاح (Journal of Economics and Administrative Sciences, 2019)
Assessing performance efficiency is critical to the management need for oversight, planning, and continuous periodic evaluation of the multiple activities of Northern Cement State Company in order to determine the level of achievement of the objectives set, and to correct the deviations and delays that the evaluation shows and limitation of liability. What cannot be measured cannot be managed. The aim of this research is to highlight the impact of using BSC, financial and non-financial, to give comprehensive and clear picture of the company's performance and to measure the quality of its performance by using six-sigma and the level of deviations in achieving the planned goals. Therefore, four-key hypotheses were formulated for the research: The first key hypothesis is that there is a correlation between BSC and strategic performance. As for the second key hypothesis, it hypothesizes that there is a significant impact of BSC with strategic performance. The third key hypothesis hypothesizes that there is a correlation between six sigma and strategic performance. The fourth key hypothesizes that there is a significant impact between six sigma and strategic performance. The research reached several theoretical and practical conclusions, the most important of which is that BSC is a complete means that contributes to the integration of financial and non- financial perceptions with strategic performance, operational and productive, to ensure that specific strategies are achieved and controlled in order to achieve the objectives set and to evaluate and develop performance in the light of those objectives. The statistical analysis of the questionnaire found that there was a relationship between BSC and strategic performance, the analysis also proved a relationship between six sigma and strategic performance.